2005
DOI: 10.2337/diabetes.54.12.3503
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Fat Mass in Interleukin-1 Receptor Antagonist–Deficient Mice

Abstract: Interleukin (IL)-1 is a regulator of inflammation but is also implicated in the control of energy homeostasis. Because the soluble IL-1 receptor antagonist (IL-1Ra) is markedly increased in the serum of obese patients and is overexpressed in white adipose tissue in obesity, we studied the metabolic consequences of genetic IL-1Ra ablation in mice. We have shown that IL-1Ra ؊/؊ mice have a lean phenotype due to decreased fat mass, related to a defect in adipogenesis and increased energy expenditure. The adipocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
72
3
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 43 publications
9
72
3
3
Order By: Relevance
“…2). Whereas Somm et al observed an augmented level of energy expenditure in Il1ra −/− mice on a normal diet [10], we only detected a significant increase in energy expenditure on a HFD; the discrepancy is probably due to differences in the diet or housing conditions. As locomotor activity was decreased in Il1ra −/− mice under HFD (Fig.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…2). Whereas Somm et al observed an augmented level of energy expenditure in Il1ra −/− mice on a normal diet [10], we only detected a significant increase in energy expenditure on a HFD; the discrepancy is probably due to differences in the diet or housing conditions. As locomotor activity was decreased in Il1ra −/− mice under HFD (Fig.…”
Section: Discussioncontrasting
confidence: 99%
“…In this report, we analysed Il1ra −/− mice on a HFD and found that they are resistant to HFD-induced obesity, which is consistent with previous reports [9,10]. The SNS is activated in these mice, resulting in the activation of BAT and emergence of multilocular BAT-like cells in WAT depots.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We also observed an increase in the mRNA level of interleukin 1 receptor antagonist (Il1rn, previously known as Il1ra) (Fig. 3a), recently shown to regulate adipogenesis, food intake and energy expenditure [32]. A similar tendency was noticed in epididymal adipose tissue (Fig.…”
Section: C3h/hej Mice Do Not Respond To Lpssupporting
confidence: 73%
“…Il1rn −/− mice, in which excess IL1 signalling may be induced, show a lean phenotype [45]. This phenotype has been associated with a defect in adipogenesis, a reduction of genes involved in lipogenesis, an increase in energy expenditure and a reduction in diurnal food intake [32]. The increase in IL1RN production in WAT may be directly involved in the phenotype obtained in TLR4 mutant mice, which exhibited both increased peripheral lipogenesis and lower thermogenesis.…”
Section: Discussionmentioning
confidence: 99%